2011
DOI: 10.1182/blood-2010-11-316158
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2 mediates the activation of human monocytes and endothelial cells by antiphospholipid antibodies

Abstract: IntroductionThe antiphospholipid antibody syndrome (APS) is characterized by clinical manifestations such as arterial or venous thromboembolism and/or recurrent pregnancy complications, as well as the presence of antiphospholipid antibodies (aPLAs). 1 Endothelial cells, monocytes, and platelets are targeted by aPLAs, and inflammatory activation of these cells has been proposed as a pathogenic mechanism. aPLAs are composed of heterogenous auto-antibodies that recognize plasma proteins bound to phospholipid surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 52 publications
3
81
0
Order By: Relevance
“…While the nature of possible first-hit conditions is still elusive, accumulating evidence, although controversial, suggest that the responses of EC, monocytes or platelets to aPLA require interactions with innate immune receptors, co-receptors and accessory proteins. As discussed above, whereas under resting conditions EC abundantly express TLR4 molecules, but little TLR2 proteins, EC activation by TNF or TLR4 ligands increases TLR2 levels [52] and aPLA-associated response of EC [34]. While the exact role of TLR4 or TLR2 in EC activation by aPLA remains to be defined, and may likely depend on the relative expression of these TLRs by EC, we propose that a first hit, such as an infectious insult, induces TLR2 up-regulation by EC through a TLR4-dependent mechanism.…”
Section: The Role Of Members Of the Tlr Familymentioning
confidence: 87%
See 3 more Smart Citations
“…While the nature of possible first-hit conditions is still elusive, accumulating evidence, although controversial, suggest that the responses of EC, monocytes or platelets to aPLA require interactions with innate immune receptors, co-receptors and accessory proteins. As discussed above, whereas under resting conditions EC abundantly express TLR4 molecules, but little TLR2 proteins, EC activation by TNF or TLR4 ligands increases TLR2 levels [52] and aPLA-associated response of EC [34]. While the exact role of TLR4 or TLR2 in EC activation by aPLA remains to be defined, and may likely depend on the relative expression of these TLRs by EC, we propose that a first hit, such as an infectious insult, induces TLR2 up-regulation by EC through a TLR4-dependent mechanism.…”
Section: The Role Of Members Of the Tlr Familymentioning
confidence: 87%
“…Sorice et al [55] have identified that TLR4, β2GP1 and annexin A2 form an activation cluster in plasma membrane microdomains of human monocytes after LPS or aPLA ligation. This study however did not evaluate the association of β2GP1 with other TLRs in lipid rafts in monocytic cells, and in particular because TLR2 and CD14 are required for aPLA recognition by monocytes and EC [34]. By using the proximity ligation assay, a technique that generates information concerning the strength of the protein-protein interactions, aPLA were found to interact more strongly with TLR2 on monocytes and cytokine activated EC than with TLR4 [34].…”
Section: The Role Of Members Of the Tlr Familymentioning
confidence: 96%
See 2 more Smart Citations
“…For prestimulation treatment, HUVECs were incubated with 100 ng/mL of recombinant HumaXpress tumor necrosis factor a (TNFa; Humanzyme, Chicago, IL) as described. 7 Production of rAAV, Empty Capsids, and MockInoculum. rAAV, empty capsids and mock-inoculum were produced in HEK293 cells (ATCC number: CRL-1573).…”
Section: Methodsmentioning
confidence: 99%